PENGARUH MANAJEMEN RANTAI PASOK BERBASIS SISTEM ERP TERHADAP KINERJA KARYAWAN PT INFINEON TECHNOLOGIES BATAM - Badra Maitri; Cindy Hartono; Fion Jennifer; Jesslyn Jesslyn; Jumi Liana; Rizni Aulia Qadri (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
A company needs good business continuity to maximize all aspects of businessactivities, therefore a structured management governance is needed. A goodenterprise resource planning system will produce a clear flow of supply chainmanagement and create good human resource performance within the company.The existence of ERP system assistance makes it easy to obtain existing informationon a company in each division with the support of a large database so that companyoperations run smoothly, such as at PT Infineon Technologies Batam which hassurvived until now. This study uses qualitative analysis methods and is in the formof descriptive information, the data obtained will be related to the theory andanalysis of the company. The results of the study show that implementing an ERPsystem at PT Infineon Technologies Batam is very beneficial for companiesbecause it can reduce costs due to continuous integration and monitoring, as wellas another factor of implementing an ERP system at PT Infineon TechnologiesBatam is being able to adjust customer interests to obtain a more efficient level inmaximizing revenue results.Keywords: Customer, Enterprise, Enterprise resource planning, Human Resources,Management, Product, Supply Chain, Technology